IMPLEMENTASI GERAKAN LITERASI SEKOLAH (GLS) DI SDN KENDALREJO 01 KECAMATAN TALUN KABUPATEN BLITAR - Ria Fajrin Rizqy Ana Ria (Universitas PGRI Adi Buana Surabaya, 2023)
The problem with GLS at SDN Kendalrejo 01 is the lack of specialized staff to manage the library. Library is one of the supporting factors of GLS program as a place to provide reading materials. The purpose of this study is to describe the implementation of the GLS program, describe the supporting factors of the GLS program, and describe the inhibiting factors of the GLS program at SDN Kendalrejo 01. The research method uses qualitative with a qualitative descriptive approach. The instruments used were observation sheets, interview guidelines, and documentation. The subjects of this research are principals, teachers and students of SDN Kendalrejo 01. The data analysis technique is data reduction, data presentation, and conclusion drawing. The results of the research on the implementation of GLS at SDN Kendalrejo 01 are based on the familiarization stage, development stage, and learning stage. At the habituation stage, the activities are 15 minutes of reading, providing reading corners in the classroom, providing magazines, providing libraries, and public involvement. At the development stage, guided reading and shared reading are carried out. At the learning stage, organizing literacy-based classes, summarizing the results of the reading that students read, and explaining the content of the reading that students read. Supporting factors for the implementation of GLS at SDN Kendalrejo 01 are the availability of libraries, reading books, mading, reading corners and active reading posters. Factors inhibiting the implementation of GLS at SDN Kendalrejo 01 are students' lack of reading habits and libraries that are not running well.